Clinical characteristics and cause analysis of false-positive results in treponemal testing among patients - Wei Wang; Xuzhou Fan; Keyi Zhou; Qianqian Chen; Xuelian Huang (Annals of Medicine)
Background Currently, there is a dearth of systematic research data on the phenomenon of false-positive reactions in treponemal tests. The aim of this study is to analyze the clinical characteristics and influencing factors associated with false-positive treponemal tests in patients, so as to enhance the diagnostic accuracy of syphilis and mitigate misdiagnosis-induced incorrect treatment.Methods From January 2017 to December 2023, a total of 759 cases with false-positive results for treponema were screened for blood transfusion, surgery, or other medical interventions at Jinling hospital. The demographic, clinical, and laboratory characteristics of patients were retrospectively analyzed to identify the risk factors associated with false-positive reactions in treponemal antibody screening.Results The results indicated that individuals under 18 years old, over 45 years old and males exhibited a higher false-positive rate for treponemal tests (p < 0.001). The false-positive rates of treponema were found to be higher in the fields of pediatrics, nephrology, and internal medicine (p < 0.05). There was no difference observed in ABO blood group distribution (p > 0.05). .Furthermore, the levels of treponema antibody and coagulation function were found to be associated with the occurrence of false-positive syphilis test results.  Multivariate logistic regression analysis indicated that ≤18 years, ≥45 years, male were independent risk factors (p < 0.01).Conclusion This study demonstrates that the false-positive rate of treponemal tests can be increased by factors such as age, gender, immune diseases, and coagulation disorders. The treponemal antibodies titer level is a valuable reference for assessing false-positive results. To enhance the accuracy of syphilis diagnosis, multiple risk factors should be considered when interpreting results from treponemal tests.